Maxillofacial Trauma and Psychological Stress - Young, Cecilia; Yeung, CYYJ (Journal of Medical and Psychological Trauma, 2018)
A review links maxillofacial trauma to psychological stress responses. It discusses screening, early interventions, and multidisciplinary care to improve recovery.
Keywords: maxillofacial trauma; psychological stress